PRICE 2020 guidelines for reporting case reports in Endodontics: a consensus‐based development. (20th March 2020) - Nagendrababu, V.; Chong, B. S.; McCabe, P.; Shah, P. K.; Priya, E.; Jayaraman, J.; Pulikkotil, S. J.; Setzer, F. C.; Sunde, P. T.; Dummer, P. M. H.
Abstract: Case reports can provide early information about new, unusual or rare disease(s), newer treatment strategies, improved therapeutic benefits and adverse effects of interventions or medications. This paper describes the process that led to the development of the Preferred Reporting Items for Case reports in Endodontics (PRICE) 2020 guidelines through a consensus‐based methodology. A steering committee was formed with eight members (PD, VN, BC, PM, PS, EP, JJ and SP), including the project leaders (PD, VN). The steering committee developed an initial checklist by combining and modifying the items from the Case Report (CARE) guidelines and Clinical and Laboratory Images in Publications (CLIP) principles. A PRICE Delphi Group (PDG) and PRICE Face‐to‐Face Meeting Group (PFMG) were then formed. The members of the PDG were invited to participate in an online Delphi process to achieve consensus on the wording and utility of the checklist items and the accompanying flow chart that was created to complement the PRICE 2020 guidelines. The revised PRICE checklist and flow chart developed by the online Delphi process was discussed by the PFMG at a meeting held during the 19th European Society of Endodontology (ESE) Biennial Congress in Vienna, Austria, in September 2019. Following the meeting, the steering committee created a final version of the guidelines, which were piloted by several authors during the writing of a case report. In order to help improve the clarity, completeness and quality of case reports in Endodontics, we encourage authors to use the PRICE 2020 guidelines.